2019
DOI: 10.1111/apt.15185
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase 3 trial: tegoprazan, a novel potassium‐competitive acid blocker, vs. esomeprazole in patients with erosive oesophagitis

Abstract: Summary Background Tegoprazan is a novel potassium‐competitive acid blocker that has a fast onset of action and can control gastric pH for a prolonged period, which could offer clinical benefit in acid‐related disorders. Aim To confirm the non‐inferiority of tegoprazan to esomeprazole in patients with erosive oesophagitis (EE). Methods In this multicentre, randomised, double‐blind, parallel‐group comparison study, 302 Korean patients with endoscopically confirmed EE (Los Angeles Classification Grades A‐D) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 25 publications
0
71
0
1
Order By: Relevance
“…11 It is an acid-resistant weak base that can remain in a highly acidic canaliculi of gastric parietal cells. 12 In animal models of GERD, tegoprazan was more potent than PPIs, and especially esomeprazole. 13 Recently, a Phase III study of tegoprazan showed good safety and efficacy compared with a traditional PPI.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 2 more Smart Citations
“…11 It is an acid-resistant weak base that can remain in a highly acidic canaliculi of gastric parietal cells. 12 In animal models of GERD, tegoprazan was more potent than PPIs, and especially esomeprazole. 13 Recently, a Phase III study of tegoprazan showed good safety and efficacy compared with a traditional PPI.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…13 Recently, a Phase III study of tegoprazan showed good safety and efficacy compared with a traditional PPI. 12 Based on these results, tegoprazan was approved for use in South Korea in July 2018. 12 During the clinical trial, researchers reported several adverse events, including diarrhoea and headaches; however, the incidence of adverse events does not appear to be significantly higher than that of traditional PPIs.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 1 more Smart Citation
“…During 2019, the number of individual downloads via Wiley Online Library (WOL) was 1,763,117 representing an increase of 17% over the same period for the preceding year. The 10 most frequently downloaded papers on WOL, published between 1st October 2018 and 30th September 2019, covered a variety of topics including prebiotics and probiotics for IBS, potassium‐competitive acid blockers in reflux disease, dietary FODMAPs, the microbiome (inevitably) and the cholestatic consequences of bodybuilding supplements . These 10 papers will be free‐access for the next 12 months.…”
mentioning
confidence: 99%
“…FODMAPs, the microbiome (inevitably) and the cholestatic consequences of bodybuilding supplements. [11][12][13][14][15][16][17][18][19][20] These 10 papers will be free-access for the next 12 months.…”
mentioning
confidence: 99%